Robot fish with two-DOF pectoral fins and a wire-driven caudal fin. (2nd January 2018) - Zhong, Yong; Li, Zheng; Du, Ruxu
Abstract: This paper presents a robot fish with a wire-driven caudal fin and a pair of pectoral fins. First, the design of the robot fish is presented. The caudal fin is driven through wire-driven mechanism. The pectoral fins can perform two degrees-of-freedom motions, i.e. flapping (roll) and feathering (pitch). The pectoral fins can move in labriform mode for propulsion, or for other purposes such as turning and diving. Second, the propulsion analysis models for caudal fin propulsion and pectoral fins propulsion are derived. Finally, three types of experiments are conducted. Experiment results show that the swimming speed of caudal fin propulsion and pectoral fin propulsion match the model predictions. Moreover, with the caudal fin propulsion alone, the robot fish can swim up to 0.66 BL/s (body length/second); with the pectoral fin propulsion alone, the robot fish can swim up to 0.26 BL/s. The pectoral fins can significantly improve the maneuverability of the robot fish. Without using the pectoral fins, the turning radius of the robot fish is 0.6 BL; with the pectoral fins, the turning radius is reduced to 0.25 BL. Abstract :